2019
DOI: 10.1038/s41598-019-47144-1
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rhythm Complexity Impairment in Patients with Pulmonary Hypertension

Abstract: Pulmonary hypertension is a fatal disease, however reliable prognostic tools are lacking. Heart rhythm complexity analysis is derived from non-linear heart rate variability (HRV) analysis and has shown excellent performance in predicting clinical outcomes in several cardiovascular diseases. However, heart rhythm complexity has not previously been studied in pulmonary hypertension patients. We prospectively analyzed 57 patients with pulmonary hypertension (31 with pulmonary arterial hypertension and 26 with chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(43 reference statements)
0
15
0
1
Order By: Relevance
“…It has shown that the complexity decreased in the presence of a systemic disease. 12,14 The main reason of the difference may be the existence of a disease in the participants and the breakdown of the balance in the systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that the complexity decreased in the presence of a systemic disease. 12,14 The main reason of the difference may be the existence of a disease in the participants and the breakdown of the balance in the systems.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Tsai et al reported that detrended fluctuation analysis shown better predictive ability for clinical outcomes when compared to traditional heart rate variability analysis methods. 14 In the literature, there are some studies which investigated heart rate variability time series with detrended fluctuation analysis and reported the accuracy of the method. 15,16 To our knowledge, there are no reports in the literature on non-linear analysis of heart rate variability used to investigate the acute effects of caffeinated beverages on cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these interpretations, experimental applications have demonstrated a degraded entropy in cardiac and postural dynamics associated with frailty, aging, impairments, or diseases [ 1 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. By contrast, high entropy is generally associated with an elevated capacity to adjust to an ever-changing environment [ 8 ], and elevated values are often observed in young healthy people [ 1 ].…”
Section: Introductionmentioning
confidence: 64%
“…However, previous HRV studies have mainly focused on linear analysis, and its ability to predict outcomes remains limited compared with non-linear HRV 8,12 . Non-linear HRV has also been studied with regards to the diagnosis and outcome prediction in many diseases with excellent results, including the outcomes of acute stroke 34 , primary aldosteronism 16 , severity of abdominal aorta calcification 35 , critical illnesses requiring extracorporeal life support 36 , post-myocardial infarction heart function 37 , and pulmonary hypertension 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Heart rhythm complexity derived from non-linear HRV measures the complexity of heart rate interval, and is composed of multiscale entropy (MSE) and detrended fluctuation analysis (DFA). Compared to linear parameters, heart rhythm complexity has shown a much greater ability to detect diseases such as end-stage renal disease, primary aldosteronism, and pulmonary hypertension 15 17 . Therefore, it would seem to be reasonable to use heart rate complexity in the detection and diagnosis of HF.…”
Section: Introductionmentioning
confidence: 99%